Social media adoption and use by public agricultural extension organizations in Thailand - Kanjina, S. (International Journal of Agricultural Technology, 2021)
This research explored the adoption and use of social media, i.e., Facebook and YouTube, by district and provincial agricultural extension offices (AEO) under Thailand's Department of Agricultural Extension (DOAE). To this end, 882 district AEO’s and 77 provincial AEO’s websites, as well as Facebook’s and YouTube’s website, were searched. Contents posted and user interactions (i.e., 'Like,' 'Comment,' and 'Share') were collected and analyzed. It was found that 566 district AEO (64.17%) and 65 provincial AEO (84.42%) adopted Facebook. However, there were ten district AEO (1.13%) and nine provincial AEO (11.68%) with full adoption and active use of Facebook. For YouTube, only some disitrct and provincial AEO started to use it, and none were active users. An analysis of the Facebook contents posted by the ten district and nine provincial AEO, who were active users, revealed that most information was theirs, and published mainly with texts and pictures. It was also found that the AEO primarily distributed information concerning the offices’ activities. This type of information may be a reason for lack of user engagement in terms of 'Comment' and 'Share.' Thus, social media adoption and use by district and provincial AEO need to be improved. A policy or directive would be necessitated to encourage the AEO to adopt social media, especially YouTube. Extension officers’ capacity building for effective social media use should be provided. Also required is a clear guideline outlining elements of social media use (for example, management of personnel or team involved, and a procedure for publishing information). It should specify a priority of data to be disseminated, which would also help the AEO to employ Facebook, YouTube, and other social media applications in ways more attractive and beneficial